2021
DOI: 10.1111/1467-9817.12369
|View full text |Cite
|
Sign up to set email alerts
|

Third graders' strategy use and accuracy on an expository text: an exploratory study using eye movements

Abstract: Background Of the myriad of reading comprehension (RC) assessments used in schools, multiple‐choice (MC) questions continue to be one of the most prevalent formats used by educators and researchers. Outcomes from RC assessments dictate many critical factors encountered during a student's academic career, and it is crucial that we gain a deeper understanding of the nuances of these assessments and the types of skills needed for their successful completion. The purpose of this exploratory study was to examine ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is possible we did not see interactive effects between comprehension monitoring behaviors and reading level because the passage-specific questions were easy and only required a yes/no response (there was a high probability of responding correctly across all participants; see Table 2) and thus did not demand more rigorous attempts to either repair or detect an error in the passages. Tremblay et al (2021) found that elementary school children were more likely to reread when responding to difficult reading comprehension questions (i.e., difficult to find the answer, needed to engage in more inferencing skills) than less difficult questions. Had we tasked participants with higher level questions (e.g., literal vs. inferential questions and questions with multiple answer responses), the comprehension monitoring behaviors may have varied by the participants’ reading level, such that the higher skilled participants would have dedicated more time to forming a coherent understanding of the entire text by demonstrating longer reread and regression path durations than the lower skilled participants.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible we did not see interactive effects between comprehension monitoring behaviors and reading level because the passage-specific questions were easy and only required a yes/no response (there was a high probability of responding correctly across all participants; see Table 2) and thus did not demand more rigorous attempts to either repair or detect an error in the passages. Tremblay et al (2021) found that elementary school children were more likely to reread when responding to difficult reading comprehension questions (i.e., difficult to find the answer, needed to engage in more inferencing skills) than less difficult questions. Had we tasked participants with higher level questions (e.g., literal vs. inferential questions and questions with multiple answer responses), the comprehension monitoring behaviors may have varied by the participants’ reading level, such that the higher skilled participants would have dedicated more time to forming a coherent understanding of the entire text by demonstrating longer reread and regression path durations than the lower skilled participants.…”
Section: Discussionmentioning
confidence: 96%
“…Participants had a 50/50 chance of guessing the correct answer and consistent and inconsistent passages comprehension scores were high ( M s = 0.80, 0.76 across all 16 passages, respectively). Future research should include more comprehension questions per passage, different formats (e.g., yes/no, multiple-choice, open-ended oral response questions), varied difficulty levels, and questions that tap into the use of different component skills (e.g., inferential questions; Tremblay et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Files were prepared prior to analysis using techniques applied in previous EM studies with children (e.g., Ardoin et al, 2016; Tremblay et al, 2021; Zawoyski et al, 2015). Specifically, fixations were aligned with regions of interest (i.e., passage words or questions and answer choices) to ensure that they would be included in data analyses.…”
Section: Methodsmentioning
confidence: 99%